Rebo Wekasan: Eksplorasi Tradisi dan Nilai Budaya di Masyarakat Desa Jepang - Kudus - Widiyaningsih, Maya; Falaq, Yusuf (Universitas Galuh, 2025)
The Rebo Wekasan tradition is a routine tradition carried out by the people of Japan Village, Mejobo District, Kudus Regency every last Wednesday in the month of Safar on the Hijri calendar. This tradition has spiritual and social meanings, one of which is as an effort to avoid all forms of disasters and calamities (bala') so that the Wali Allah pray to Allah SWT. to avoid unwanted things. This study aims to describe in depth the series of events, meanings, and changes that occur in the implementation of this tradition. The research method used by the author is a qualitative method and a phenomenological perspective. The techniques used by the author are observation, in-depth interviews and documentation. The results of the study show that this tradition is still preserved with various series of events such as completing the Al-Qur'an, parades and distribution of salamun water. This tradition also discusses the meaning and changes that occur due to adapting to the times. This activity is needed in order to increase spiritual values, social values for the community. Research is expected to provide a broad understanding of this tradition so that the community is encouraged to preserve local traditions as Indonesian cultural heritage.